2021
DOI: 10.18271/ria.2021.232
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a formulation of dry sweet butifarra made with LLama meat, pecans and kañiwa

Abstract: In the formulation of dried sweet sausage, pork meat and fat are traditionally used, which can be replaced by healthy products such as pecans (Carya illinoinensis) and kañiwa (Chenopodium pallidicaule); as well as llama meat (Lama glama) that is low in fat and cholesterol. For this reason, the present investigation aimed to optimize a formulation of dried sweet sausage considering three main components: llama meat, kañiwa flour and pecans. The D-Optimal mixture design method of the Design-Expert®7 program was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…De Carvalho et al [55] reported that chewiness values were very variable (between 10.37 and 98.70 N•mm) in fresh lamb sausages due to the different percentages of pecans in the formulations, with the optimum formula, containing 20% of pecans, having a value of 12.12 N•mm. Salva Ruiz et al [56] also reported similar chewiness values (14.19 N•mm) in llama sausages with pecans (Carya illinoinensis) and kañiwa (Chenopodium pallidicaule Aellen) as fat substitutes. The results of this study were different from those reported by Alves et al [57], who observed a decrease in chewiness when green banana flour was used as a fat substitute in bologna-type sausages.…”
Section: Textural Changesmentioning
confidence: 74%
“…De Carvalho et al [55] reported that chewiness values were very variable (between 10.37 and 98.70 N•mm) in fresh lamb sausages due to the different percentages of pecans in the formulations, with the optimum formula, containing 20% of pecans, having a value of 12.12 N•mm. Salva Ruiz et al [56] also reported similar chewiness values (14.19 N•mm) in llama sausages with pecans (Carya illinoinensis) and kañiwa (Chenopodium pallidicaule Aellen) as fat substitutes. The results of this study were different from those reported by Alves et al [57], who observed a decrease in chewiness when green banana flour was used as a fat substitute in bologna-type sausages.…”
Section: Textural Changesmentioning
confidence: 74%